Russia's 1999–2000 election cycle and the politics-banking interface - Koen Schoors; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
We investigate whether lending by the dominant Russian state bank, Sberbank, contributed to Vladimir Putin's ascent to power during the presidential elections of March 2000. Our hypothesis is that Sberbank corporate loans could have been used as incentives for managers at private firms to mobilize employees to vote for the incumbent regime. In line with our proposed voter mobilization mechanism, we find that the regional growth of Sberbank corporate loans in the months before the presidential election is related to the regional increase in votes for Putin and to the regional increase in voter turnout between the Duma election of December 1999 and the presidential election of March 2000. The effect of Sberbank firm lending on Putin votes was most pronounced in regions where the governor was affiliated with the regime and in regions with extensive private employment. The effect was less apparent in regions with many single-company towns, where voter intimidation is sufficient to get the required result. Additional robustness checks and placebo regressions confirm the main findings. Our results support the view that additional Sberbank corporate loans granted prior to the March 2000 presidential election facilitated Putin's early electoral success.
URN:NBN:fi:bof-201711021663
Keywords: G21; P34; 330